1991
DOI: 10.1063/1.347243
|View full text |Cite
|
Sign up to set email alerts
|

Barrier inhomogeneities at Schottky contacts

Abstract: We present a new analytical potential fluctuations model for the interpretation of current/voltage and capacitance/voltage measurements on spatially inhomogeneous Schottky contacts. A new evaluation schema of current and capacitance barriers permits a quantitative analysis of spatially distributed Schottky barriers. In addition, our analysis shows also that the ideality coefficient n of abrupt Schottky contacts reflects the deformation of the barrier distribution under applied bias; a general temperature depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,104
4
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,498 publications
(1,156 citation statements)
references
References 39 publications
44
1,104
4
4
Order By: Relevance
“…Figure 1h shows the temperature-dependent values of the diode derived from the J-V characteristics. The Richardson plot suggests that the current transport is governed by thermionic emission since the diffusion transport is less sensitive to temperature 37 . The large deviation at low temperatures can be explained by the barrier height fluctuation model, that is, the barrier height follows a Gaussian distribution, j eff ¼ j m -qs 2 /(2k B T), where j eff is the effective barrier height, j m is the mean barrier height and s is the s.d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1h shows the temperature-dependent values of the diode derived from the J-V characteristics. The Richardson plot suggests that the current transport is governed by thermionic emission since the diffusion transport is less sensitive to temperature 37 . The large deviation at low temperatures can be explained by the barrier height fluctuation model, that is, the barrier height follows a Gaussian distribution, j eff ¼ j m -qs 2 /(2k B T), where j eff is the effective barrier height, j m is the mean barrier height and s is the s.d.…”
Section: Resultsmentioning
confidence: 99%
“…The large deviation at low temperatures can be explained by the barrier height fluctuation model, that is, the barrier height follows a Gaussian distribution, j eff ¼ j m -qs 2 /(2k B T), where j eff is the effective barrier height, j m is the mean barrier height and s is the s.d. 37 . It is found that for the diode with an IGZO thickness of 80 nm and a diameter of 1 mm, the mean barrier height is 1.40 eV with a s.d.…”
Section: Resultsmentioning
confidence: 99%
“…[181] Inhomogeneities in MIS interfaces can easily dominate net transport across them. [151,152] This is found even at the nanoscopic level. Thus, the conductance of isolated styrene [27] or acetone [182] molecules, adsorbed on Si, is affected strongly by the chemical conditions of neighboring Si atoms, which act as gate for transport across the adsorbed molecules.…”
Section: Imperfections In the Monolayermentioning
confidence: 92%
“…[44,63,90,150] SBH(J 0 ) < SBH(C 0 ) suggests an inhomogeneous barrier. [151,152] Surprisingly, for Hg/alkyl-n-Si MOMS SBH(J 0 ) $SBH(C 0 )) [19,135] but this is simply because both the width of the space charge (C 0 ) and the semiconductor transport (J 0 ) saturate at similar values (strong inversion). In any case, SBH > E G /2 presents strong support for inversion.…”
Section: Extraction Of the ''Semiconductor Barrier Height'' (Sbh)mentioning
confidence: 99%
“…barrier height determined from zero bias intercept assuming thermionic emission as current transport mechanism is well below the measured BH and the weighted arithmetic average of the barrier heights [18,19]. Furthermore, the surface damage at the metal-semiconductor interface affects the I-V measurements because defects may act as recombination centers for trapassisted tunneling currents.…”
Section: Diale Fd Auret / Physica B ] (]]]]) ]]]-]]]mentioning
confidence: 99%